Nilai-Nilai Pendidikan Dalam Balian Tantulak Ambun Rutas Matei Bagi Masyarakat Hindu Kaharingan di Kota Palangkaraya Raya - Pranata Pranata (Jayapangus Press, 2022)
The development of the times that are increasingly turning into an obligation for Hindu Kaharingan always to maintain and preserve a ceremonial tradition related to the teachings of their religion so that their generations do not forget the ceremony. Likewise, followers of the Hindu Kaharingan religion in Palangka Raya City who always carry out the balian tantulak ambun rutas matei ritual will always exist and develop to future generations of Hindu Kaharingan not forget it. The research was conducted in the city of Palangka Raya in 2020, using a qualitative descriptive method. Determining the informants used purposive sampling, considering that the informants were selected by researchers who carried out the research and understood the implementation of balian tantulak ambun rutas matei. The implementation of balian tantutulak ambun rutas matei is usually carried out after three days of death and burial. It is carried out by a base of 3-5 people and for 1 full day. The educational values ​​that can be studied are educational values ​​that can be explored in implementing the balian tantulak ambun rutas matei ceremony, namely Tatwa values, Moral values ​​, and Upakara Psychomotor values. These values ​​will be passed on to the next generation of Hindu Kaharingan so that the balian tantulak ambun rutas matei ceremony is not extinct.